2019
DOI: 10.20473/j.djmkg.v52.i3.p117-121
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Applied Behavior Analysis (ABA) with regard to tooth brushing in autistic children

Abstract: Background: Children demonstrating autistic spectrum disorders tend to be uncooperative when receiving dental treatment. Actions as simple as brushing the teeth with a prophylactic brush can constitute complex processes for children with such conditions. Applied behavior analysis (ABA) can train children in new positive behavior and it is, therefore, anticipated that an ABA-based approach iscapable of influencing the behavior of individuals with autistic spectrum disorder. Purpose: This study aimed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, research in dental setting is limited (Table 1). Melati et al., 2019 adopted the approach to assess the behavior of autistic children in regard to prophylactic brushing with favorable results 38 . Furthermore, Fageeh et al., 2021 conducted a study evaluating the effectiveness of ABA in dental practice on knowledge regarding oral health hygiene with a significant increase following the intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research in dental setting is limited (Table 1). Melati et al., 2019 adopted the approach to assess the behavior of autistic children in regard to prophylactic brushing with favorable results 38 . Furthermore, Fageeh et al., 2021 conducted a study evaluating the effectiveness of ABA in dental practice on knowledge regarding oral health hygiene with a significant increase following the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Melati et al, 2019 adopted the approach to assess the behavior of autistic children in regard to prophylactic brushing with favorable results. 38 Furthermore, Fageeh et al, 2021 conducted a study evaluating the effectiveness of ABA in dental practice on knowledge regarding oral health hygiene with a significant increase following the intervention. The authors concluded that utilization of ABA through avatars and videos significantly helped improve knowledge regarding oral health hygiene among cooperative autistic children.…”
Section: Applied Behavior Analysis (Aba)mentioning
confidence: 99%
“…Autism is a disorder of nerve development that causes children to seem unable to connect with others [1] , as if they live in their own world. Autism in male children is 3-4 times higher than female children.…”
Section: Introductionmentioning
confidence: 99%